New species of deep-sea Antipatharians from the North Pacific (Cnidaria: Anthozoa: Antipatharia), Part 2 - Opresko, Dennis M.; Molodtsova, Tina N. (Zootaxa, 2021)
Five new species of deep-sea antipatharian corals are described from the North Pacific primarily collected off the coast of Alaska and on adjacent seamounts. All the species are referred to the family Schizopathidae. Described as new are: Alternatipathes mirabilis, Bathypathes ptiloides, Bathypathes tiburonae, Bathypathes alaskensis, and Parantipathes pluma. Illustrations of the type material of Bathypathes patula, B. patula var. plenispina and B. tenuis are provided for comparative proposes. Bathypathes patula var. plenispina is here recognized as a species distinct from B. patula, and B. tenuis is considered incertae sedis due to the poor condition of the type material.